используя фсу преобразовать выражение в многочлен стандартного вида: (x-2)^2(x+2)^2

0 голосов
45 просмотров

используя фсу преобразовать выражение в многочлен стандартного вида:

(x-2)^2(x+2)^2


Алгебра (29 баллов) | 45 просмотров
Дано ответов: 2
0 голосов
Правильный ответ

(x-2)²·(x+2)² = 

= (x-2)·(x-2)·(x+2)·(x+2) =

= [(x-2)·(x+2)]·[(x-2)·(x+2)] =

= (x²-4)·(x²-4) =

= (x²-4)² =

= x⁴ - 8x² + 16

или

(x-2)²·(x+2)² =

 = (х² - 4х + 4)·(х² + 4х + 4) =

 = х⁴ - 4х³ + 4х² + 4х³ - 16х² +16х +4х² -16х +16 =

= x⁴ - 8x² + 16

 

(145k баллов)
0 голосов

(x-2)^2(x+2)^2=((x-2)(x+2))^2=(x^2-4)^2=x^4-8x^2+16

Ответ:x^4-8x^2+16 

(436 баллов)